2012
DOI: 10.1016/j.jbi.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Interface design principles for usable decision support: A targeted review of best practices for clinical prescribing interventions

Abstract: Developing effective clinical decision support (CDS) systems for the highly complex and dynamic domain of clinical medicine is a serious challenge for designers. Poor usability is one of the core barriers to adoption and a deterrent to its routine use. We reviewed reports describing system implementation efforts and collected best available design conventions, procedures, practices and lessons learned in order to provide developers a short compendium of design goals and recommended principles. This targeted re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
267
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(277 citation statements)
references
References 78 publications
4
267
1
2
Order By: Relevance
“…It is possible that physicians staffing these EDs have different knowledge or beliefs about decision tools than physicians from other practice settings. Even still, it is hard to justify the expen- diture and potential decision-support fatigue to create such systems given the small number of low-risk UGIB patients who are seen in general and even smaller number who are admitted [34]. While there may always be room for improvement, we observed a rate of only 2 avoidable admissions per year, making it difficult to suggest that more uniform application of GBS would substantially change healthcare expenditures.…”
Section: Discussionmentioning
confidence: 74%
“…It is possible that physicians staffing these EDs have different knowledge or beliefs about decision tools than physicians from other practice settings. Even still, it is hard to justify the expen- diture and potential decision-support fatigue to create such systems given the small number of low-risk UGIB patients who are seen in general and even smaller number who are admitted [34]. While there may always be room for improvement, we observed a rate of only 2 avoidable admissions per year, making it difficult to suggest that more uniform application of GBS would substantially change healthcare expenditures.…”
Section: Discussionmentioning
confidence: 74%
“…Poor usability is one of the core barriers to adoption and a deterrent to DSS use. It is found that implementation efforts of highly usable IS and collected best available design conventions, procedures, practices and lessons learned in order to provide developers a short compendium of design goals and recommended principles [15]. The function of DSS is to help their users to make more effective decisions by providing information in a way that actively assists the decision process.…”
Section: Results and Findingsmentioning
confidence: 99%
“…It has been suggested that underutilization or ignoring of CDSS interventions could be due, at least in part, to gaps in the logic presentation [41]. Participants in the development iteration were reluctant to trust non-standard warfarin doses when they had no access to the original algorithm or the algorithm website.…”
Section: Discussionmentioning
confidence: 99%
“…Our results of initial skepticism are similar to those reported in a study that implemented a personal digital assistant mechanism to support warfarin dosing [40]. In that study, some viewed the dosing assistant as a tool for providing better, safer care, while others with more experience prescribing warfarin felt the intervention had limited positive impact.It has been suggested that underutilization or ignoring of CDSS interventions could be due, at least in part, to gaps in the logic presentation [41]. Participants in the development iteration were reluctant to trust non-standard warfarin doses when they had no access to the original algorithm or the algorithm website.…”
mentioning
confidence: 99%